The level of technical and specific skill efficiency in youth class female artistic gymnasts - Omorczyk, J.; Ambrozy, T.; Bujas, P.; Puszczalowska-Lizis, E. (Journal of Kinesiology and Exercise Sciences, 2014)
Research aim. Evaluation of the level of technical efficiency in youth class female gymnasts based on the results of selected specific fitness tests. Material and methods. The research included 24 girls aged 7-8 who practice artistic gymnastics in TS Wis³a Kraków. In order to diagnose the level of technical efficiency and specific fitness, tests developed by the Methodology and Training Commission of the Polish Association of Female Gymnastics (PZG) were used. Results. A high level of technical efficiency was found in each all-around gymnastic event. A low performance in some specific fitness tests was observed. There were statistically significant relationships between the technique of exercises in particular gymnastic events and specific fitness test results. Summary. All tested gymnasts are characterized by high and similar levels of technical efficiency. Most specific fitness tests show significant differences between results obtained by the gymnast. The observed statistically significant correlations indicate that in women`s artistic gymnastics specific fitness tests should be used as early as at the stage of basic training.